The Strategy of Young Citizens in the Field of Unanswered Demands: A Qualitative Study in Yazd City - Fezzeh Abolhasani; Mahnaz Farahmand; Hossein Afrasiabi; Seyed Reza Javadian (Strategic Research on Social Problems)
IntroductionUnderstanding and addressing citizens' demands is crucial for effective policymaking and strengthening the relationship between the government and the public. This, in turn, can increase public satisfaction and trust in the government's role, position, and performance, ultimately contributing to the dynamism and development of society. Conversely, ignoring citizens' demands can lead to disruptions in the citizenship process, destructive actions by citizens, and unnecessary social costs, ultimately perpetuating underdevelopment. Therefore, the stability and order of any society depend on respecting citizens' rights, providing platforms for their realization, and fostering mutually responsive actions by satisfied citizens. Citizens' reactions can manifest in both conventional, law-abiding actions, and unconventional actions aimed at challenging the status quo. The non-fulfillment of citizens' demands and unmet needs can lead to a wide range of constructive and destructive actions, which this study sought to identify and understand. By examining the relationship between citizens' demands, government responsiveness, and societal outcomes, this research aimed to contribute to the development of more effective policymaking and the strengthening of the government-citizen relationship. Ultimately, this knowledge can support the creation of a more stable, equitable, and prosperous society.  Materials and MethodsThis qualitative study aimed to describe and analyze the demands of young citizens and identify the strategies they employed when facing unmet demands. The research utilized a content analysis approach. The data were collected through semi-structured interviews with 30 young people aged 18-35 residing in the city of Yazd. The interviews were conducted in person during the year 2023. Throughout the interview process, the researchers made concerted efforts to build trust and gain the participants' satisfaction by emphasizing ethical commitment, confidentiality, and the principle of secrecy. Participants were given the option to discontinue the interview at any point if they wished to do so. After the interviews were completed, the data were transcribed and analyzed using the MAXQDA software. This approach allowed for a thorough examination and categorization of the themes and patterns that emerged from the participants' responses. By employing this qualitative methodology, the researchers were able to gain in-depth insights into the perspectives and experiences of young citizens, capturing the nuances and complexities of their demands and the strategies they utilized when faced with unmet needs. The findings of this study can contribute to a deeper understanding of the relationship between young people and the government and inform the development of more responsive policies and initiatives.Discussion of Results & ConclusionThe data analysis revealed several key themes regarding the demands of young citizens, including negation of demands, realization of subjectivity, social empowerment, and identification of capital-building measures. Additionally, the strategies employed by young people in the face of unmet demands were categorized as boundary activism, civil disobedience, structural empowerment, pragmatic engineering, and identification of exclusionary deprivation. The demands raised in this research align with Marshall's tripartite framework of civil, political, and social rights. Citizens’ initial reaction to unmet demands was often characterized by silence, stemming from frustration and a sense of established failure frequently expressed with the phrase "nothing". These findings resonated with Habermas's theory of legitimacy crisis, which posits that citizens in contemporary societies face crises, such as the legitimacy crisis of social structures due to tensions, conflicts, and social inequalities. The data suggested that citizens were demanding the cultivation of a collective spirit, which depended on trust in institutions that could promote coherence, trust, and social hope through scientific and efficient means. In conclusion, this study provided valuable insights into the complex and multifaceted nature of young citizens' demands and the strategies they employed when faced with unmet needs. The findings underscored the importance of fostering responsive and legitimate governance structures that could address the evolving expectations and aspirations of young people, ultimately contributing to a more stable, equitable, and prosperous society.Drawing on Giddens' theory of the duality of structure and agency, realization of citizenship as a component of modern societies and maintenance of social balance were contingent upon 3 key conditions: an effective government, a market-based economy, and a civil society capable of subjectivity. However, according to the citizens in this study, none of Giddens' three conditions had been adequately met and civil society had gradually been marginalized by a dominant minority. Another common demand expressed by the participants was a focus on developing human capital as a component of sustainable development. The importance of this demand lay in the need to create the necessary conditions for its realization. Regrettably, governments sometimes fail to fulfill their role of addressing the needs of young people, leaving their demands unmet. In such situations, a wide range of constructive and destructive actions may emerge. Some young citizens, upon recognizing inefficiency of the existing structures and institutions, come to a sense of helplessness in resolving crises and addressing issues. This can lead to a dualistic state of detachment from structures, while continuing their ordinary lives without political or civic involvement. This phenomenon can be likened to the concept of isolation or chosen isolation proposed by Robert Merton (1968) or in Karsitzers' view, the prevalence of fatalism. These findings underscored the critical importance of responsive and accountable governance that could effectively address the evolving needs and aspirations of young citizens. Fostering an environment that nurtures human capital development and empowers civil society to play an active role in shaping social outcomes is essential for maintaining social balance and promoting sustainable development.Citizens sometimes express their resistance in everyday, informal, and unorganized ways to confront power structures and systems. According to the data, citizens might engage in civil disobedience, political criticism, and provocation in society. In some cases, they showed their resistance through riots, violent protests, and defiance in political matters. Without visible violence, citizens might also resist by neglecting their civic duties, such as not paying taxes and fees, violating city laws, or bypassing organizations hypocritically. Additionally, citizens might express their anger by destroying public facilities or engaging in vandalism. Aligning with Derrida's theory of subversion, citizens might also seek to change gender norms or subvert dominant religious and cultural discourses. For instance, they had decoded hidden messages from the prevailing religious discourse and acknowledged changes in the status of the hijab, clothing, and performance of religious rituals, despite the emphasis of structures on observing Islamic norms. Owing to the Islamic nature of the government, they attributed the non-fulfillment of promises to Islam and chose to revise their values in the face of unmet demands. Furthermore, citizens might reinterpret themselves and employ two-faced tactics to confront the structures they faced. Another strategy was the "trap of deprivation", where citizens, under the existing pressures, developed a destructive perception of structures and resorted to harmful coping mechanisms, such as drug and alcohol consumption, dropping out of school, taking on multiple jobs, selling family assets, suicide, or selling body parts. These actions, while providing temporary relief, often exacerbated their deprivation in the long run as the theory of multiple pressures suggests. These findings highlighted the complex and multifaceted ways, in which citizens exercised resistance and coped with the challenges they encountered within the sociopolitical landscape. Understanding these strategies is crucial for developing responsive and inclusive policies that can address the evolving needs and concerns of the citizenry.The citizens' statements pointed to a complex societal landscape marked by poverty, marginalization, unequal access to resources, dominance of ideology over public space, marginalization of certain groups, and inefficiency and misconduct of institutions. These challenges had forced citizens to adopt a range of positive and negative strategies, each with the potential to both help and hinder societal progress. In some cases, citizens' remedial actions attempted to address gaps and alleviate deprivations, thereby serving the broader interests of the society. However, in other instances, their passivity and inaction could weaken social cohesion. Similarly, their efforts to reinforce societal structures might lead to increased tension and violence, while their self-destructive behaviors and destructive coping mechanisms could exacerbate their own deprivations, trapping them deeper within the cycle of crises and entrenched deprivation. Identifying the full spectrum of citizen demands and strategies is crucial for developing effective policymaking. By understanding the nuanced ways, in which citizens navigate their challenges, policymakers can work to create a foundation for positive change and strengthen societal resilience, preventing the proliferation of undesirable strategies that can further destabilize the social fabric. The key lies in crafting responsive policies and interventions that address the root causes of the citizens' concerns, empower marginalized communities, and foster an environment that cultivates positive, constructive, and sustainable forms of civic engagement. This holistic approach can help break the cycle of crisis and deprivation, ultimately leading to a more equitable and resilient society.